SELF-ESTEEM OF STUDENTS RAISED BY SINGLE MOTHERS AT MTsN 3 AGAM - Mawar Mustika Rahmi; Khairani Khairani (Jurnal Neo Konseling, 2021)
This research is motivated by an incident that occurred in MTs Negeri 3 Agam students where students were faced with a single mother's family condition, they tended not to accept the situation that occurred to their family which was shown by an attitude like feeling jealous of their friends who had a complete family. This study aims to describe the self-esteem of students raised by single parent mothers at MTs Negeri 3 Agam based on aspects of general self-esteem, social self-esteem and personal self-esteem. The method used in this research is quantitative method with descriptive type. The subjects in this study were students who were raised by single parent mothers at MTs Negeri 3 Agam, totaling 86 students registered in the 2020/2021 academic year. Data collection techniques used a questionnaire with a Likert scale model and to analyze data using a percentage formula. The research findings reveal that (1) the self-esteem of students raised by single parent mothers at MTs Negeri 3 Agam as a whole is in the medium category with a percentage of 43.02%, (2) students' self-esteem seen from the general self-esteem aspect is at medium category with a percentage of 40.70%, (3) students 'self-esteem seen from the social self-esteem aspect is in the medium category with a percentage of 38.37%, (4) students' self-esteem seen from the personal self-esteem aspect is at medium category with a percentage of 34.88%.